The Effect of Financial Literacy and Financial Attitudes on Financial Management with Financial Inclusion as an Intervening Variable - Ardanari, Tri Meidiana; Widagdo, Bambang; Nurjannah, Dewi (Universitas Muhammadiyah Malang, 2024)
This study aims to determine the influence of financial literacy and financial attitudes towards financial management and financial inclusion which are used as intervening variables. The population in this study were SMEs in the Trade Sector in Malang City using a purposive sampling technique. The sample of this research is 109 respondents. The results showed that financial literacy has a significant effect on financial management, financial attitudes have a significant effect on financial management, financial literacy has a significant effect on financial inclusion, financial attitudes have a significant effect on financial inclusion, financial inclusion has no significant effect on financial management, and financial inclusion not mediating financial literacy and financial attitudes towards financial management.